2015
DOI: 10.1242/jcs.178889
|View full text |Cite
|
Sign up to set email alerts
|

Orc5 induces large-scale chromatin decondensation in a GCN5-dependent manner

Abstract: In eukaryotes, origin recognition complex (ORC) proteins establish the pre-replicative complex ( preRC) at the origins, and this is essential for the initiation of DNA replication. Open chromatin structures regulate the efficiency of preRC formation and replication initiation. However, the molecular mechanisms that control chromatin structure, and how the preRC components establish themselves on the chromatin remain to be understood. In human cells, the ORC is a highly dynamic complex with many separate functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Mechanistically, multi-mono-ubiquitylation of the ORC complex may also alter the local chromatin environment around origins, making them more accessible to limiting firing factors. Consistent with this idea, it was recently reported that ORC5 interacts with the histone acetyl-transferase GCN5/KAT2A, making origins more accessible for activation 36 . ORC5 multi-mono-ubiquitylation could promote this interaction, opening the local origin chromatin environment and stimulating origin activation.…”
Section: Discussionmentioning
confidence: 54%
“…Mechanistically, multi-mono-ubiquitylation of the ORC complex may also alter the local chromatin environment around origins, making them more accessible to limiting firing factors. Consistent with this idea, it was recently reported that ORC5 interacts with the histone acetyl-transferase GCN5/KAT2A, making origins more accessible for activation 36 . ORC5 multi-mono-ubiquitylation could promote this interaction, opening the local origin chromatin environment and stimulating origin activation.…”
Section: Discussionmentioning
confidence: 54%
“…Subunits of ORC have also been implicated in centrosome biology or cytokinesis (31)(32)(33) so it would be interesting to examine whether these functions account for slow proliferation. In addition, we are currently investigating whether other functions of ORC, like its role in epigenetics (34)(35)(36), is responsible for the decrease in proliferation despite the near normal replication initiation. As we have noted, decrease of ORC subunits decreases cell proliferation without affecting replication initiation.…”
Section: Discussionmentioning
confidence: 99%
“…In higher eukaryotes, the positioning of replication origins is not dictated by a single DNA sequence motif and appears to be more dependent on the chromatin environment. For instance, it has been suggested that ORC triggers a permissive chromatin environment through the direct recruitment of histone acetyltransferases, such as GCN5 [33]; [34]). Moreover, the OGRE/G4 element upstream of the pre-RC is nucleosome-free, whereas the IS contains a labile nucleosome that might be removed during the initiation step.…”
Section: Epigenetic Marksmentioning
confidence: 99%